Implementasi Metode Analytical Hierarchy Process (AHP) dalam Sistem Pendukung Keputusan untuk Pemilihan Handphone - Priyatna, Ade; Sanwani, Sanwani; Azizah, Ayu (Journal of Information System Research (JOSH), 2024)
Currently, many people experience confusion when choosing a smartphone that suits their daily activities and needs due to the vast number of brands and models available in the market. The diverse specifications and uses of smartphones often lead consumers to purchase products that do not meet their needs. To address this issue, a decision support system was designed to help buyers select the right smartphone. This research uses the Analytical Hierarchy Process (AHP) method to analyze quantitative data, enabling the determination of criteria and alternative smartphone choices that are suitable.In the process of data entry and processing, criteria and alternatives are established to facilitate the selection of a smartphone. One common challenge in designing decision models is the inability of the model to reflect all real variables, which can result in inaccurate decisions. Therefore, it is essential to design a flexible model capable of accommodating various relevant variables. Additionally, each stored model must be accompanied by detailed information and comprehensive explanations to ensure users understand the proposed decision-making process and its basis.This research can provide an effective solution in smartphone selection, offering clear and structured guidance for consumers to make more accurate decisions based on their individual needs. The research results show that the Xiaomi brand achieved a score of 0.90, indicating that Xiaomi is the most chosen brand in the best smartphone category.